Strength and compressibility charactrisitcs of kaolin mixed with bottom ash - Jorat, Mohammad Ehsan (2010)
Coal is one of the world’s most important sources of energy, fuelling almost 40% of electricity worldwide. The burning of coal produced coal ash that mostly consists of Fly Ash and Bottom Ash. Bottom Ash (normally recognized as coal combustion residues from pulverized fuel power stations) has been categorized as solid garbage. However, the utilization of Bottom Ash in construction-related applications has received some attention within the last decade. This project aimed at determining the strength and compressibility of Kaolin, mixed with 25 %, 50% and 60% of bottom ash. Kaolin, in powdered forms, was mixed with Bottom Ash and compacted at optimum moisture content. The strength and compressibility of the compacted samples were determined from direct shear test, unconsolidated undrained triaxial tests, and one-dimensional consolidation test, besides the California Bearing Ratio and permeability tests. It was observed that the granular nature of Bottom Ash increased the friction angle of Kaolin, increased the permeability and expedite the consolidation rate. However, the addition of 25% Bottom Ash gives the highest shear strength of Kaolin while the addition of 60% Bottom Ash gives the highest permeability and coefficient of consolidation. This results show that Bottom Ash can be used to increase the strength of soil, in particular the soft soil and also could expedite the consolidation of the soil. This is due to the granular nature of the materials that could increase the voids in the mixtures and also contribute to increase in friction angles.